Soundscape research on the Gezi Park – Tunel Square route - Bahalı, Sercan; Tamer-Bayazıt, Nurgün (Elsevier BV, 2017)
Abstract The properties of urban sound environments are subject to several factors, such as physical, social, cultural features of the city and people. Hence, urban soundscape studies are important for understanding the sound environments in a city from different points of view. In this study, soundscape research was designed and applied with practices, regarding the Gezi Park - Tunel Square route, specifying key locations as Gezi Park, Taksim Square, Galatasaray Square, and Tunel Square. This study is primarily reliant on the “soundwalk method,” which combines the ‘Positive Soundscape Project’ and ‘Schafer’s World Soundscape Project.’ Soundwalks were applied in the research field by silently walking along the route, and after the walk, questions about the soundscape characteristics of the route and its perceptual features were answered by the participants. With the results of questionnaires, and by means of semantic descriptors (which were used by participants to express the soundscapes of key locations), soundscape characteristics on the route were discussed. Subjective parameters and psychoacoustic parameters which was obtained via binaural recordings and post-signal analysis were compared with regards to their effects on soundscapes. The aim was to find out the perceived soundscape characteristics of four key locations and factors that affect soundscape classification along the route.